Studi Gaya Desain Interior Gereja Katolik Santo Yusuf Ronggowarsito dan Kapel Susteran OSF di Gedangan Semarang - Setiabudi, Leonardo (Intra, 2013)
St. Joseph Catholic Church and Gedangan OSF Convent is a historic building in Semarang and is the first building to be a key witness to the journey and the work of the Catholic convent at the OSF. Intake of these two objects because the both, have a strong historical narrative continuity besides both buildings is a very magnificent object at that time and its implementation using a design style that developed in Europe. This study investigates the design elements of the style and how the application of force on the element interior design at St. Joseph Catholic Church (GKSY) and Gedangan OSF Convent in Semarang with descriptive research methods. The subject of the research focused on the aspect of the form to the scope of the research, building typology, organization of space, interior space-forming elements, transition elements, elements of space filler and decorative elements. The results showed that the interior of the GKSY building was influenced by design style of Early Chrsitian, Colonial, Renaissance, Gothic and Neogothic. For the OSF Convent building have been influenced by design style of Romanesque, Byzantine, Colonial, Renaissance, Baroque and Gothic, and Neogothic.